PROGRESSING STUDENTS’ MOTIVATION IN LEARNING ENGLISH BY USING HYPNOSIS (HYPNOLEARNING) AT STUDENTS OF STAN 2 JILC PERINTIS MAKASSAR - Hamzar Acha (ETERNAL (English, Teaching, Learning and Research Journal), 2019)
ABSTRACT, This article provides a description of the students’ motivation in learning English by using hypnosis (hypnolearning) at the students of STAN 2 of JILC Perintis, Makassar 2010/2011. The population of the research consisted of the students of STAN 2 of JILC Perintis, Makassar in academic year of 2010/2011. It consisted of one class. The number of the students was 20 and the sample of this research was total sampling. It means that all students of STAN 2 of JILC Perintis, Makassar were taken as samples namely 20 students. In this research, the data was collected by using questionnaire. The questionnaire was used to obtain data on students’ motivation by using hypnosis (hypnolearning). It consisted of 20 items. Based on the data obtained, this article discovered that students were motivated in learning English by using hypnosis (hypnolearning). The data showed that the students always choose “agree” in every item of the questionnaire which was given. It indicated that the level of the students’ motivation by the students of STAN 2 of JILC Perintis, Makassar in learning English by using hypnosis (hypnolearning) was “agree”. Keywords: Students’ Motivation, Hyposis, English Learning Style